Revealing adolescent drug trafficking and addiction: Exploring school disciplinary and drug issues in the federal territory of Kuala Lumpur and Selangor, Malaysia - Norita Anak Jubit; Masron, T; Redzuan, M. S; Ahmad, A; Yoshinari, K (ResearchGate, 2024)
Previous studies have predominantly concentrated on drug trafficking and addiction amongst adults, with a relative dearth of research specifically dedicated to adolescents. However, it is crucial to recognise that drugrelated issues amongst adolescents necessitate unique attention and understanding. This study sets out to identify high clusters of drug trafficking and addiction in Kuala Lumpur and Selangor, and scrutinise their relationship with schools that have disciplinary and drug-related issues. By analysing the data, the study seeks to comprehend the correlation between these high clusters and the presence of disciplinary problems and drug issues within schools in the region. Local Indicator Spatial Autocorrelation was utilised in this study to identify the patterns of adolescent drug trafficking and addiction in Kuala Lumpur and Selangor. The Local Indicator Spatial Autocorrelation analysis (LISA) from 2015 to 2020 disclosed consistent high-high clusters of adolescent drug trafficking and addiction in Pantai, Ampang, Jinjang, Tun H. S. Lee, Pudu, and Cheras areas. These clusters indicate a concentrated prevalence of drug-related activities amongst adolescents aged 17 years old and below. Secondary School of SMK Sri Pantai in Pantai faces disciplinary challenges related to drug issues, underscoring the importance of providing support for a safe learning environment. In contrast, SMK Bandar Ampang has managed to maintain a drug-free environment despite being in a high-high cluster area. SMK Dato Ibrahim Yaacob in Jinjang, along with SMK Dato Onn, Tun H. S. Lee, Cheras, and SMK Cochrane Perkesa, are closely associated with drug issues amongst adolescents. Schools grappling with discipline issues and drugrelated problems are notably affected by their geographical locations. It's worth mentioning that a majority of these institutions are positioned in areas with a high concentration of drug trafficking and addiction, amongst adolescents (17 years old or younger). These findings emphasise the need for preventive measures and support to ensure student well-being and safety.